SEASON OF GLANDULAR FEVER AS A RISK FACTOR FOR MULTIPLE SCLEROSIS. Issue 11 (14th October 2015) - Downham, Christina; Visser, Elizabeth; Vickers, Mark; Counsell, Carl
Abstract : Background: Glandular fever (GF) is a known risk factor for multiple sclerosis (MS) but it is unclear if the risk varies by season due to vitamin D-related variations in immune responses. Methods: Patients with MS diagnosed between 16–60 yrs were identified from the Clinical Practice Research Datalink (CPRD) along with up to six controls per case, matched by age, gender, general practice and duration of observation in CPRD prior to the date of diagnosis (index date). The numbers of patients and controls with a coded diagnosis of GF prior to the index date were identified and the date of GF diagnosis noted. Multivariable logistic regression analysed whether cases were more likely than controls to have GF in winter rather than summer, adjusted for age, gender and region. Results: 9247 cases (118 with GF) and 55033 controls (483 with GF) were included. GF was more common in MS cases than controls (odds ratio [OR] 1.77, 95% CI 1.53–2.05) but winter exposure was not associated with a higher risk of MS than summer (OR 1.09, 95% CI 0.72–1.66). Conclusions: Glandular fever in winter as opposed to summer does not appear to be associated with a greater risk of developing MS.